Triterpenoid Fraction Antimalarial Activity Test from Methanol Extract Made by Leaf Artocarpus camansi Against Plasmodium Berghei by In Vivo - Ramadhani Sucilestari; Dwi Soelistya D J; Imam Bachtiar (Natural B, Journal of Health and Environmental Sciences, 2013)
Malaria disease is still a serious health problem in Indonesia. This study aimed to determine the antimalarial activity of triterpenoid compound fraction of A. camansi leaf methanol extract to P. berghei of in vivo. This experiment of using research a completely randomize design (CRD) with four different doses (0.1 mg/kg BW, 1 mg/kg BW, 10 mg/kg BW, 100 mg/kg BW) and one negative control group (1 % CMC). The results show that triterpenoid compound fraction of A. camansi leaf methanol extract was effective to reduce parasite activity of P. berghei. The most effective dose was 100 mg/kg BW for three days with daily treatment after the mice was infected by parasite.